Growth status and academic performance in Brazilian school age children: growth retardation impairs mathematical, but not reading and spelling abilities Crescimento e desempenho acadêmico em escolares brasileiros: retardo no crescimento interfere com a matemática mas não com a leitura e a escrita - Gilberto N.O. Brito; Mercedes de Onis (Arquivos de Neuro-Psiquiatria)
AIM: To assess the effect of child growth status on academic achievement and the association between child growth and academic standing. METHOD: The heights of 722 middle-school children were measured using standard procedures and height-for-age z (HAZ) scores were calculated based on an international reference. Academic performance was assessed by an adaptation of the Wide Range Achievement Test (WRAT3) composed of Reading, Arithmetic and Spelling. RESULTS: Children in the group with higher HAZ scores performed better than children in the group with lower HAZ scores only on the Arithmetic subtest. This finding was confirmed by a multiple regression model analysis of the data. In addition, only performance on the Arithmetic subtest was positively associated with HAZ. CONCLUSION: These results indicate that growth retardation impacts specifically on the development of arithmetic (numeracy) skills and are consistent with a three-fold model of life course influences on health including latency, cumulative and pathway effects. OBJETIVO: Examinar o efeito do crescimento no desempenho acadêmico e a associação entre crescimento e competência acadêmica. MÉTODO: A estatura de 722 escolares da rede pública de Niterói foi medida através de procedimentos padronizados e escores padronizados da estatura para a idade (HAZ) foram calculados com base em referência internacional. O desempenho acadêmico foi avaliado através de uma adaptação do Wide Range Achievement Test (WRAT3) composto de leitura, aritmética e ditado. RESULTADOS: Crianças com HAZs mais elevados apresentaram um desempenho melhor do que crianças com HAZs mais baixos somente na aritmética. Este achado foi confirmado por uma análise de modelo de regressão múltipla dos dados. Ademais, somente o rendimento em aritmética mostrou uma associação positiva com HAZ. CONCLUSÃO: Os resultados indicam que o retardo no crescimento impacta especificamente no desenvolvimento de competência em matemática e são consistentes com um modelo de influências durante o curso da vida que inclui efeitos de latência, cumulativos e de trajetória.